Are free-floating planktonic hydroids (Cnidaria, Hydrozoa) common components of the pelagic fauna from the South Brazilian Bight?. (23rd June 2015) - Cabral, Ana Caroline; Nogueira Júnior, Miodeli; Nagata, Renato Mitsuo; Brandini, Frederico Pereira
Abstract : We analysed 267 zooplankton samples collected in the South Brazilian Bight (SBB; 23–27°S) to determine whether hydroids, typically benthic, are common components of the pelagic SBB. Two species, Clytia arborescens, recorded for the first time in the Atlantic Ocean, and Clytia sp. were identified. While these planktonic hydroids were frequent or relatively so in shallow shelf waters ( 23% of the samples <50 m isobaths, and 5% of the samples >100 m), abundances were low (up to 61 hydranths m −3 ) suggesting a low trophic impact. Such colonies are probably fragments of benthic colonies detached by storms and/or tides. Given the good condition of the coenosarc, existence of gastric content, and presence of reproductive structures, development of these species appears to be normal in the pelagic environment. Existence in the plankton may increase their capacity for dispersion.